One tough dame the life and career of Diana Rigg - Pilato, Herbie J. 1960- (University Press of Mississippi, 2024)
"One Tough Dame: The Life and Career of Diana Rigg covers the full spectrum of the esteemed actor's life and career. This chronicle combines insight from rare, archived interviews she granted (on video, via the University of Kent and Oxford Union conversations, and several in print discussions), applicable recollections culled from various media outlets through the decades, all-new, never-before-published recollections from those who knew her best, and fresh perspectives from several leading entertainment historians and sources. With exclusive commentary from those like Rupert Macnee and Ray Austin, actors Samuel West, Bernie Kopell, Barbara Barrie, Juliet Mills, John Schuck, Damon Evans, and director Bruce Beresford, and director/producer and James Bond documentarian David Naylor, One Tough Dame delivers an in-depth perspective of the beloved, brave, brilliant (by American and British standards and definitions), and no-holds-barred thespian of the highest degree."
Keywords: Rigg, Diana -- 1938-2020; Rigg, Diana (1938-2020); Actors / Great Britain / Biography; Biografie